POLITICAL COMMUNICATION IN THE MASS MEDIA (Framing Analysis News of East Java Governor Election 2013 on Malang Daily Morning Post and Memo Arema at 12th up to 26th August 2013 Period) - Sepri Setiawan; Anam Miftakhul Huda; Gigih Mardana (JARES (Journal of Academic Research and Sciences), 2016)
In 2013 becomes a democracy party for East Java citizens to be re-elected as the governor candidate in 2008. There are four couples who propose themselves as the vice of Governor. The results showed that Malang Daily Morning Post tends to proclaim the East Java Governor Election campaign 2013 to the demand services to be shared more, this media preaches candidates with more portion by blowing up candidate campaign activities. So it makes the news unbalanced. And Daily Morning Memo Arema is able to maintain its neutrality with a slogan that is critical and outspoken, despite having a partnership with a KarSa ’s couple, this media still criticizes when the couple is in violation. Keywords: Political, Communications, Mass Media.